Prototype of Early Detection and Home Fire Extinguishing System Based on IoT and GPS - Syarif, Peto; Mairizwan, M; Asrizal, A; Yohandri, Y (Department of Physics – Universitas Negeri Padang UNP, 2025)
Fire is a disaster that can occur at any time, anywhere, without realizing it, causing material loss and even loss of life. Based on data from the Padang City Fire Department, there will be 198 fire cases in 2023 and 230 in 2022. Even though it has decreased, the risk of fire is still a serious threat. The main cause of fires is delays in detection and handling due to delays in information and inaccurate positioning. Therefore, this research aims to design a prototype system for early detection and home fire extinguishing based on IoT and GPS. This research is a type of engineering research; the system design includes an IR fire sensor for fire detection, an MQ-135 sensor for CO2 gas detection, and a NEO-7M GPS module for location tracking. This system uses an Arduino Uno microcontroller and an ESP32 NodeMCU for data processing and IoT connectivity. The research results show that the system performance specifications have good linearity sensor characteristics (R² close to 1), Blynk and WhatsApp application interfaces for monitoring and alarm notifications, as well as a 50x50x50 cm prototype equipped with a water pump and fan. Design specifications indicate a voltage measurement accuracy of 96.27% and a CO2 concentration of 97.56%. For voltage measurements, the precision is 99.81% and the CO2 concentration is 98.31%. The actuator operates at a predetermined set point and performs well. The early warning system test worked well with a time lag of 5–15 seconds.